Assessment of common maternal risk factors related to gestational diabetes among pregnant women in KAMC, Riyadh - SHALABI, MAHA MATOUQ; ISMAEL, RAWAA ISMAEL MOHAMMAD; HABIB, FARIDA MAHMOUD; PRINCE, JYOTHI PETER; ALENEZY, ASMA JADAAN; ALHMOOD, KHADEJA ABDULLAH; ALMOTEIRI, MEAAD TALAL (Journal of medical and pharmaceutical sciences, 2018)
The current study this was conducted to assess common maternal risk factors for gestational diabetes shared among pregnant women in King Abdullah Medical City (KAMC), Riyadh.Using the descriptive analytical approach, the current study involved all pregnant women attending King Abdulaziz Medical City in Riyadh. A sample of 450 pregnant women was selected according to stratified random sampling method. A structured questionnaire for assessing the common maternal risk factors for gestational diabetes mellitus was designed and filled by 449 from the research sample.The study has shown that women diagnosed with gestational diabetes mellitus (GDM) could be at high risk for future diabetes. Besides, GDM differs in a direct proportion with the spread of type 2 diabetes. The study found a relationship between GDM and obesity, the history of the family with diabetes, age, and physical activities. Moreover, the results have shown that the research sample lack knowledge concerning gestational diabetes i.e. diet and exercises. In this regard, the researcher recommends raising the women awareness of GDM and taking additional care of pregnant women and especially those having GDM.
Keywords: Maternal Risk Factors; Gestational Diabetes; KAMC; Riyadh